Development Of A Portable 3D Printer For Medical Modelling - Sin, Chia Ling (2020)
The application of rapid prototyping such as 3D printing in medical modelling helps the doctor to have a better illustration on the structure by looking into 3D printed model. Besides, during COVID-19 pandemic period, 3D printing technology solved the shortage of supply chain for PPE, tester or spare parts for medical equipment. The most common used 3D printing method is FDM, fused deposition modelling and Cartesian 3D printer is the most ordinary 3D printer in the market. However, the heavy and bulky design of 3D printer cause the printer inconvenient to be carried, which cannot meet the needs of mobile printing. This research aims to review on the development of portable 3D printer that optimize the space usage. The portable 3D printer is designed in such that the Z-gantry axis is able to be folded down during non-usage period. The folding mechanism apply the concept of ball plunger spring that is applied in the mechanism of the folding handle of a luggage at the locking position when it is extended. The hardware parts of the portable 3D printer consists of aluminium profiles, 3D printed parts and acrylic sheet. In the other hand, RAMPS 1.4 is used to as control board together with Arduino Mega 2560 board and A4988 Stepper Motor Driver. The firmware of the portable 3D printer implements Marlin x2.0 and Pronterface is used to simulate the printing. Fine adjustment has been made on hardware and firmware to achieve the best quality of printing. The developed portable 3D printer is 390 mm